2008
DOI: 10.1007/s00415-008-0801-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate of non-operated meningiomas

Abstract: The mean volumetric growth rate was significantly greater than the planimetric growth rate, suggesting that volumetric measurement conveys more information and is superior in assessing tumor growth. This information could have clinical value in determining the frequency of follow-up imaging and the urgency of surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…The planimetry method has been widely used to calculate the volume of meningiomas in previous studies (3,4,(11)(12)(13)(14)(15); however, the details of the procedure depend on each investigator. The thickness of MRI used in the planimetry method is often not regarded in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The planimetry method has been widely used to calculate the volume of meningiomas in previous studies (3,4,(11)(12)(13)(14)(15); however, the details of the procedure depend on each investigator. The thickness of MRI used in the planimetry method is often not regarded in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have used the ABC/2 formula (2,25,26) or the original ellipsoid volume (10,19,27) to measure the volume of intracranial tumors, including meningiomas, few studies have evaluated the accuracy of ABC/2 formula for intracranial tumors. The planimetry method presents a more approximate volume for the real tumor and has been applied in many studies (3,4,(11)(12)(13)(14)(15); however, this method is more cumbersome than the ABC/2 method. In addition, the thickness of MRI used to calculate tumor volume differs between each investigator.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies measured various aspects of the growth rate [3,4,5,6,7,10,11,14,17,19,21,22,23] (Table 4). Six measured growth rate in diameter.…”
Section: Results:-mentioning
confidence: 99%
“…Zeidman et al found a 3.82% per year difference between relative growth in planimetric versus volumetric measures with a p<0.0001. [23] Ten out of the twenty studies utilized planimetric measurements of initial size of tumor while eight studies used volumetric measures. Niiro et al found a significant different in initial size in diameter between growing and nongrowing tumors reporting a p-value of 0.016 [13].…”
Section: Initial Tumor Size:-mentioning
confidence: 99%
See 1 more Smart Citation